Relationship between internet addiction and healthy lifestyle behaviors of nursing students - Kırağ, Nükhet; Güver, Yusuf (Journal of Dependence, 2019)
Objective: This research aims to determine the relationship between healthy lifestyle behaviors and internet addiction of university nursing students.Method: This cross - sectional study was conducted on 29 September - 10 October 2019 with 291 students studying at the Faculty of Nursing of Aydın Adnan Menderes University. Sociodemographic form, Healthy Lifestyle Behaviors II (HLB) and Internet Addiction Scale were used to collect data.Results: The students were of 76.3% girls and 99% were single. It was seen that there was a statistically significant relationship between the presence of friends, perception of health status and diagnosis of mental illness on the healthy lifestyle behaviors of nursing students. Gender, health status and income status were found to be effective on students' internet addiction level. It was found that there was a negative correlation between healthy lifestyle behaviors and spiritual development and interpersonal relationships and a positive correlation between healthy lifestyle behaviors and all sub-dimension.Conclusion: There was a relationship between healthy lifestyle behaviors and internet addiction level. It is thought that developing healthy lifestyle positively for university students is a protective factor against internet addiction.
Keywords: Nursing; addiction; student; internet addiction